Rhamnolipids as biosurfactants from renewable resources: Concepts for next-generation rhamnolipid production - Henkel, Marius; Mueller, Markus M.; Kuegler, Johannes H.; Lovaglio, Roberta B. [UNESP]; Contiero, Jonas [UNESP]; Syldatk, Christoph; Hausmann, Rudolf (Elsevier B.V., 2012)
Several microorganisms are known to produce a wide variety of surface-active substances, which are referred to as biosurfactants. Interesting examples for biosurfactants are rhamnolipids, glycolipids mainly known from Pseudomonas aeruginosa produced during cultivation on different substrates like vegetable oils, sugars, glycerol or hydrocarbons. However, besides costs for downstream processing of rhamnolipids, relatively high raw-material prices and low productivities currently inhibit potential economical production of rhamnolipids on an industrial scale. This review focuses on cost-effective and sustainable production of rhamnolipids by introducing new possibilities and strategies regarding renewable substrates. Additionally, past and recent production strategies using alternative substrates such as agro-industrial byproducts or wastes are summarized. Requirements and concepts for next-generation rhamnolipid producing strains are discussed and potential targets for strain-engineering are presented. The discussion of potential new strategies is supported by an analysis of the metabolism of different Pseudomonas species. According to calculations of theoretical substrate-to-product conversion yields and current world-market price analysis, different renewable substrates are compared and discussed from an economical point of view. A next-generation rhamnolipid producing strain, as proposed within this review, may be engineered towards reduced formation of byproducts, increased metabolic spectrum, broadened substrate spectrum and controlled regulation for the induction of rhamnolipid synthesis. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Rhamnolipid; Biosurfactant; Pseudomonas aeruginosa; Metabolic engineering; Renewable resource; Renewable feedstock